Studi Masyarakat Sosial Dalam Persfektif Kelompok Sosial Dan Stratifikasi Sosial - Sahlan Sahlan (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
A group or group is a collection of individuals who interact with each other, generally only to do work, to improve relationships between individuals, or it could be both. A group at one time distinguished collectively, a group of people who have togetherness in common activities but with the smallest direction of interaction. A social group is a collection of people who have a shared awareness of membership and interact with each other. Group is created by society. Groups can also influence the behavior of their members. Social groups are things that are commonly known in society, both ancient and present. As a result, things like this cause conflicts in society due to differences in the meaning of social groups themselves, even though in Islamic teachings there are differences in gender, differences in skin color, race, ethnicity, nation and customs which are unique in themselves so that in God's eyes a noble human being is humans who have a pious and pious personality and behave well with others. Sociologically, the definition of a social group is a collection of people who have relationships and interact with each other and can result in the growth of shared feelings.